PENGARUH PEMBERIAN ISCHEMIC COMPRESSION DAN STRETCHING UNTUK MENGURANGI NYERI MYOFASCIAL TRIGGER POINT OTOT UPPER TRAPEZIUS PADA PEGAWAI KLAIM BPJS DI RUMAH SAKIT GRANDMED LUBUK PAKAM TAHUN 2020 - Miftahul Zannah; Rio Septian; Timbul Siahaan; Isidorus Jehaman; Siti Sarah Bintang (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2020)
Background: Myofascial Trigger point syndrome is a local pain trigger point characterized by irritation, inflammation, and swelling. The main problem is that when the emphasis is made, it creates a hypersensitive pain. Myofacial trigger point occured by adhesions, increase by malnutritions and oxygen to ischemic. The problems are pain on muscle cervical contraction and spasm, tenderness, tightness, stiffness, decrease muscle strength.Physiotherapy modalities that can be used for Myofascial Trigger point syndrome are Ischemic Compression and Stretching exercise. Objectives: The study aims to determine influence of Ischemic Compression and Stretching exercise in patients with the myofascial trigger point syndrome with pain of the Upper Trapezius muscle Trigger Point at the Grandmed Lubuk Pakam Hospital. Research method: uses quasi experiments with one group pre test and post test. Samples for this research are 20 respondents got Ischemic Compression and Stretching exercise intervention. Respondents divided into two variable, dependent variable got stretching and ischemic compression method and independent variable is measure for pain in myofascial trigger point syndrome. Results: Hypotheses test results with the Wilcoxon saigned rank test result obtained by P-value â‰¤ Î± (0.000 < 0.05). Mean of pain based on Numeric rating scale before intervention (pre test) is 4,60 and after interventiom (post test) is 2,00. Conclusion:According to experimental decisions, there is an influence Ischemic Compression and Stretching exercise to decrease pain in the Myofascial trigger point syndromeof the upper trapezius muscle trigger point at the Grandmed Lubuk Pakam Hospital.